An open outdoor algal growth system of improved productivity for biofuel production. Issue 1 (14th August 2018) - Kannan, Dheeban Chakravarthi; Venkat, Devi
Abstract: BACKGROUND: Microalgae are among the most promising options for renewable fuel production in the future. Translating high laboratory yields to outdoor productivity has been a major challenge. Outdoor sunlight intensity is much greater than the saturation light intensities of algae. An open outdoor growth system design has been developed based on systematic distribution of sunlight to improve the productivity. RESULTS: The first stage of the light‐distribution design (1800 L) yielded 1.5–2.0 times better productivity than a standard open system, and the next stage (630 L) yielded 2–3 times better productivity. Productivities up to 36–42 g m −2  day −1 were obtained in a region where the climatic conditions are mostly adverse for algal growth. Comparison with other similar climatic conditions validated the performance improvement of the growth system over a wide range. Light distribution profiles illustrated the distribution patterns and gave cues for further improvement. Cost comparison of light distribution against the additional land and infrastructure indicates promising reductions. CONCLUSION: The performance improvement shown by the designed growth system is significant and shows good potential for advancement of outdoor algal production for biofuels and related products. © 2018 Society of Chemical Industry